Developing of applications on Google’s Android powered devices and Arduino-powered platforms 1 - Liu, Lun Hsin (2015)
The widespread usage of increasingly powerful smartphone devices provides great potential for the development of innovative and useful applications in many areas and industries. Augmented Reality (AR) is a technology that combines Virtual Reality (VR), Artificial Intelligence (AI) and Computer Graphics (CG). In AR apps, rendering data are overlapped on to the real world environment in an interactive manner. The Internet of Things (IoT) is a computing idea that portrays a future where ordinary physical objects will be connected with the Internet and have the capacity to recognize themselves to different devices. [1] The combination of AR and IoT has already impacted human’s daily life, and this technology will continue to be a valuable and important tool to bring more convenience and benefits for different areas. The purpose of this project is to designs and develop an Android AR application that allows the user to view the live information from sensor nodes. There are two phrases for this project. Phrase 1 is to display the sensors’ data in an intuitive graphical interface by recognising AR markers or QR code marker on the sensor nodes. After this is achieved, markerless AR be implemented and the application will be able to display the data without any physical markers. The application will first display an AR camera view when launched. When the user points a smartphone at an AR marker which contains the sensor node ID, it will be read and sent to database to retrieve the information of specified sensor node. The information will then be displayed on the AR view. Due to the limitation of AR libraries, Phrase 2 which is markerless AR recognition was not able to be completed. However, possible solution for future development was suggested in this report.